2007
DOI: 10.1136/jnnp.2004.052654
|View full text |Cite
|
Sign up to set email alerts
|

A model of personality change after traumatic brain injury and the development of the Brain Injury Personality Scales

Abstract: The information obtained from the interviews with the TBI survivors and the SOs produced two models with a similar structure: three superordinate factors of personality items (affective regulation, behavioural regulation and engagement) and one superordinate factor of items relevant to mental state (restlessness and range of thought). Despite the similarity in structure, the content of the information obtained from the two interviews was different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…In another study of the Five Factor Model, the results showed an increase in Neuroticism and decreases in Extraversion and Conscientiousness, but these changes were no different between the patients with TBI and those with other bodily injuries [62]. Finally, investigators developed Brain Injury Personality Scales based on information provided by the patients and their SO's [63]. Although the patients and SO's gave different information, factor analysis revealed the importance of the personality factors of affective regulation, behavioural regulation and engagement.…”
Section: Discussionmentioning
confidence: 96%
“…In another study of the Five Factor Model, the results showed an increase in Neuroticism and decreases in Extraversion and Conscientiousness, but these changes were no different between the patients with TBI and those with other bodily injuries [62]. Finally, investigators developed Brain Injury Personality Scales based on information provided by the patients and their SO's [63]. Although the patients and SO's gave different information, factor analysis revealed the importance of the personality factors of affective regulation, behavioural regulation and engagement.…”
Section: Discussionmentioning
confidence: 96%
“…While some of these scales relate to personality (e.g., scale 0 assesses introversion), the MMPI-2 clinical scales were designed to measure psychopathology. Though it is important to assess psychopathology after TBI (studies often show elevated post-injury psychopathology rates; Silver et al, 2010), uncovering the mechanisms of post-TBI personality disturbance probably requires using personality measures (e.g., the NEO PI-R for general personality, Costa & McCrae, 1992; experimental NEO PI-R, Haigler & Widiger, 2001, or MMPI-2 PSY-5 scales, Harkness, McNulty, & Ben-Porath, 1995, for maladaptive personality; or Brain Injury Personality Scales for personality disturbances directly related to TBI, Obonsawin et al, 2007).…”
Section: Limitations Within the Literaturementioning
confidence: 98%
“…Its descriptions range from simple delineations (e.g., personality change vs. no change; Brooks & McKinlay, 1983;Weddell & Leggett, 2006) to comprehensive models (e.g., Max, Castillo, Lindgren, & Arndt, 1996;Obonsawin et al, 2007). The few available comprehensive frameworks were developed mainly in the service of creating assessment tools.…”
Section: Difficulties In Categorizing Post-tbi Personality Disturbancesmentioning
confidence: 99%
See 2 more Smart Citations